Photosynthetic adjustment after rehydration in Annona emarginata - Mantoan, Luís Paulo Benetti [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP]; Macedo, Ana Claudia [UNESP]; Ferreira, Gisela [UNESP]; Boaro, Carmen Silvia Fernandes [UNESP] (Springer Nature, 2016)
Reports indicate that Annona emarginata is tolerant to drought and is also used as an alternative rootstock for atemoya under drought conditions. The photosynthetic process can be adjusted after rehydration, resulting on total or partial recovery. The aim of this study was to determine if A. emarginata shows adjusts in gas exchange and the chlorophyll a fluorescence pattern after rehydration. During water deficits, the gas exchange and water content in the leaf decreased. However, after 5 days of rehydration, the water content in the leaf recovered and rehydrated plants presented the water use efficiency better than irrigated plants. Further remaining gas exchange parameters were lower in relation to irrigated plants. In chlorophyll a fluorescence, the rehydrated plants showed higher dissipation of light energy as heat, maintaining high activity of photoprotection. After rehydration, A. emarginata shows a positive correlation between transpiration and CO2 assimilation rate, which optimize the water use efficiency. Thus, A. emarginata presents adjustments in gas exchange and photochemical process, resulting on a possible long-term photosynthetic acclimation to water deficiency.
Keywords: Annonaceae; Drought; Photosynthesis; Recovery; Rootstock; Water deficit